Perioperative Anticoagulation and Risk Assessment: Building a Bridge Over a STREAM - Anil Harrison; Sushil Rayamajhi (Journal of Nepal Medical Association)
Perioperative care requires a comprehensive assessment of the risks of bleeding and thrombosis. The 2022 CHEST Guidelines offer an empirical foundation for customized treatment using clinical judgment and risk assessment based on CHA2DS2-VASC and HAS-BLED scores. Despite the ease of access to anticoagulation guidelines, decision-making remains challenging, particularly when determining the necessity of bridging therapy with unfractionated or low-molecular-weight heparin. To facilitate this decision, we provide a mnemonic, STREAM, that highlights high-risk situations that require bridging. These include recent stroke or transient ischemic attack, severe thrombophilia, rheumatic valvular disease, recent venous thromboembolism, atrial fibrillation with high CHA2DS2-VASC scores, and mechanical heart valves. This mnemonic offers physicians a methodical approach to optimize perioperative anticoagulation control while minimizing the risk of hemorrhage and thrombosis.